Macro News and Exchange Rates in the BRICS - Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the effects of newspaper headlines on the exchange rates visa-a-vis both the US dollar and the euro for the currencies of the BRICS (Brazil, Russia, India, China and South Africa). The data are daily and cover the period 03/1/2000-12/5/2013. The estimated VAR-GARCH(1,1) model allows for both mean and volatility spillovers and for the possible impact of the recent financial crisis as well. The results differ across countries, but provide in a number of cases evidence of significant spillovers, whose strength appears to have increased during the crisis. Further, given the increasingly global role of these countries, their FX markets have become more responsive to foreign news.
Keywords: C32; F36; G15; 330; BRICS; exchange rates; GARCH model; macro news